Investigating Dismal River obsidian use in central Nebraska. (3rd July 2019) - Hughes, Richard E.; Geib, Phil R.; Ziska, Courtney L. C.
Abstract : Nineteen obsidian artifacts from surface contexts of probable Dismal River complex sites in the Sand Hills of Nebraska were analyzed via energy dispersive X-ray fluorescence (EDXRF) spectrometry. The artifacts derive from six distinct geological volcanic glass sources. One of the artifacts was made from ash-flow tuff obsidian of the Brown's Bench chemical type and another from Wild Horse Canyon, Utah obsidian, representing the first documented use of these western source materials in Nebraska. Southwestern obsidian sources are less well represented than those to the west of Nebraska in this study sample, indicating that more than one pattern of obsidian use and conveyance may have existed during the Dismal River complex.